Animated Pathway Interactive Map - Budiansyah, Arie; Candra, Rudi Arif; Gani, Taufiq Abdul; Ilham, Dirja Nur; Rusdiana, Siti (Sinkron : jurnal dan penelitian teknik informatika, 2019)
A map is one of the cartographic scientific products that is used as a guide to access locations or places. The use of information technology and computer systems in cartography can increase the value of map products to be interactive and can be accessed online via the internet. This interactive map of the Unsyiah Director Office building is the development of an interactive map product of the author with the addition of an animated pathway from the reference point to the location point. With these additions, it will be easier for visitors to access the location